2019
DOI: 10.32474/acr.2019.02.000143
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Gender Based Studies of Diagnosis and Treatment of Cardiovascular Disease in Last 20 Years

Abstract: In a study conducted by Kwok Leung Ong et al. [6], they suggested that sex hormones could be responsible for gender differences in coordination with blood pressure. Even though there

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Gender-based variations in the pathophysiology, symptomatology, presentation, efficacy of diagnostic tests, and response to pharmacological interventions exist. Our systematic review of gender-based studies of diagnosis and treatment of CVD in the last 20 years shows discrepancies in outcomes of CAD between men and women ( 7 , 9 15 ). Studies suggest that knowledge and awareness of bias reduce discrimination and therefore our publication will aid in decreasing physician bias.…”
Section: Introductionmentioning
confidence: 94%
“…Gender-based variations in the pathophysiology, symptomatology, presentation, efficacy of diagnostic tests, and response to pharmacological interventions exist. Our systematic review of gender-based studies of diagnosis and treatment of CVD in the last 20 years shows discrepancies in outcomes of CAD between men and women ( 7 , 9 15 ). Studies suggest that knowledge and awareness of bias reduce discrimination and therefore our publication will aid in decreasing physician bias.…”
Section: Introductionmentioning
confidence: 94%
“…Underlying risk factors for cardiovascular disease (CVD) in general have different physiological effects on the two genders. Our systematic review of gender-based studies of diagnosis and treatments of CAD over the last 20 years [ 3 ] demonstrated multiple significant studies exist in targeting gender-based discrepancies. The complete causes of these discrepancies and the effect age hold treatment delay in age groups have yet to be fully elucidated and require further analysis to design interventions and structures to combat bias.…”
Section: Introductionmentioning
confidence: 99%